Severe Disseminated Paracoccidioidomycosis with Chylous Ascites and Cutaneous Lesion in an Immunocompetent Woman: A Case Report - Kajita, Mariana Soares; Teodoro, Victoria Cassioti; Lago, Marianna Martins; Patzina, Rosely Antunes; Ponce, César Cilento; Khoury, Zarifa (Brazilian Journal of Case Reports, 2026)
A 45-year-old premenopausal woman, without known immunodeficiencies and originating from and living in an endemic area for paracoccidioidomycosis, with a history of bariatric surgery and nonalcoholic fatty liver disease (NAFLD), initially presented with asthenia and prostration, progressing over approximately 7 months to lymphadenopathy, headache, ascites, lower limb edema, and a scalp skin lesion. She was hospitalized with suspected malignancy, and lymph node biopsy revealed a fungal etiology, while serology for Paracoccidioides spp. was positive. Despite two treatment cycles with Amphotericin B followed by oral therapy with Sulfamethoxazole/Trimethoprim and Itraconazole, ascites persisted. Eleven months after symptom onset, she was admitted to Instituto de Infectologia Emílio Ribas for investigation of severe paracoccidioidomycosis associated with cutaneous lesions and ascites. Clinical, laboratory, and radiological investigations identified chylous ascites, as well as lymph node, pulmonary, and cutaneous dissemination. Lymph node and skin biopsies, together with serological tests, confirmed paracoccidioidomycosis. Prolonged treatment (6 weeks) with Amphotericin B transitioned to oral therapy resulted in clinical and serological resolution. This case highlights the rarity of severe chronic paracoccidioidomycosis with chylous ascites and cutaneous involvement in a woman of reproductive age without acquired immunodeficiencies, suggesting the influence of genetic, postsurgical, and epidemiological factors.